Sexual and domestic violence among women attending a STI/AIDS clinic in Vitória, Brazil - Raquel Barbosa Miranda; Maria Alix Leite Araújo; Bettina Moulin Coelho Lima; Roumayne Fernandes Andrade; Nathalia Lima; Angélica Espinosa Miranda (DST, 2022)
Introduction: Violence against women can take several forms; ranging from sexual harassment, discrimination, and discounting to even more serious forms such as those physical and sexual in nature. Objective: To describe the frequency of domestic and sexual violence reported by women attending a sexually transmitted infections (STI) clinic in Vitória, Brazil. Methods: Women attending the STI/AIDS clinic during the period of study were invited to participate and were interviewed after signing a written consent form. The assessment questionnaire included information on socio-demographic characteristics such as risk behaviors for STI and clinical, domestic, and sexual violence reports. Results: A total of 276 (96.8%) women agreed to participate, of which 109 (39.5%) were HIV-positive and 167 (60.5%) were HIV-negative. History of domestic violence was reported by 52.6% of women, mainly related to alcohol abuse (41.6%), use of illicit drugs (27.2%), and psychiatric problems (25.3%). Previous sexual violence was reported by 28.6%, and 31.6% of these cases occurred when the participants were younger than 14 years old. A total of 69.2% of women were between 18 and 34 years old; 11.2% reported frequent use of alcohol; 21% use of illicit drugs and 2.2% reported injectable drugs. Regarding the use of condoms, HIV-positive women were less afraid to ask the partner to use condoms compared with HIV-negative women (31.2% versus 41.9%, p=0.022). Conclusion: History of domestic and sexual violence was frequently reported in this study. The effects of violence to women’s physical and mental health are widely known as a serious public health problem. In addition to its importance, violence is an invisible problem in our society and we need to learn how to approach it during clinical consultation.